Trends in the use and dual use of factory-made combustible cigarettes, other tobacco products and electronic cigarettes: Results from South African Social Attitudes Surveys during 2007 to 2018 - Catherine O. Egbe; Siphesihle Gwambe; Mukhethwa Londani; Olufemi Erinoso; Olalekan A. Ayo-Yusuf (Tobacco Induced Diseases)
Introduction Using more than one tobacco product increases the risk of tobaccorelated diseases. We investigated trends in the prevalence and dual use of factory-made (FM) cigarettes, other tobacco products, and electronic cigarettes (e-cigarettes) in South Africa over a 12-year period.